Sistem Pendukung Keputusan Pemilihan Mobil Bekas Menggunakan Metode Analythical Hierarchy Process - Gushelmi Gushelmi; Dodi Guswandi (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2021)
Showroom Ragasa Motor Padang is a showroom that sells various types of used cars. The old system of selecting used cars in The Ragasa Motor Padang Showroom is that customers come directly to the address of this Showroom and the selection process is still done by manual means. With the development of internet technology today is increasing rapidly and in order to be accessible to everyone, the AHP can do a comparison of the criteria in pairs on the selection of used cars and can determine the consistency of the comparison data paired with a threshold value of < 0.1. The purpose of this research is to make it easier for customers to choose used cars quickly and accurately, as well as the application of programs used to make it easier for customers to use them. The result of this study is the SPK System that was built to be able to take the decision of the selection of used cars in the Showroom Ragasa Motor Padang with the selection of the 2nd alternative with a value of 2.55 as the best choice.